Extreme Weather Events Interact With Local Contexts to Alter the Frequency of Firearm Violence and Child Maltreatment in Wayne County, Michigan - Rebeccah Sokol; Cynthia Gerlein‐Safdi; Michelle Degli Esposti; Mildred Wallace (GeoHealth, 2025)
Abstract Climate change is creating more frequent extreme weather events, but impacts on violence are not well understood. We explored associations of extreme weather with firearm violence and child maltreatment in Wayne County, Michigan. To understand contextual influences, we estimated models using data from before (2018–2019), during (March 2020–March 2021), and after (2022–2023) the onset of the COVID‐19 pandemic. In both 2018–2019 and 2022–2023, firearm violence was lower in the first couple days after extreme weather compared to no prior extreme weather (relative risks [RR]: 0.44–0.54; 95% confidence intervals [CI]: 0.21–0.37, 0.79–0.90), with the influence waning over the following week. We did not observe any reduction, however, during the first year of the COVID‐19 pandemic. Associations differed for child maltreatment. In 2018–2019, we observed no change in maltreatment in the days following extreme weather. Yet, during the first year of the COVID‐19 pandemic, child maltreatment was higher over the 10 days following extreme weather (RR: 1.24; 95% CI: 0.97, 1.58). In 2022–2023, child maltreatment was lower following extreme weather events, but this finding is likely an artifact of reduced reporting after extreme weather during this period. In Wayne County, extreme weather immediately reduced firearm violence, with effects waning as people likely resumed regular activities. The first year of the COVID‐19 pandemic suspended this influence, as extreme weather may not have changed daily activities beyond pandemic‐related disruptions. For child maltreatment, however, extreme weather created accumulating risk over several days when it disrupted an already stressed environment.